The hinode mission - Sakurai, Takashi (Springer, 2008)
The Hinode (Solar-B) mission: an overview - Data archive of the Hinode mission - The X-Ray telescope (XRT) for the Hinode mission - The Hinode X-Ray telescope (XRT): Camera design, performance and operations - The EUV imaging spectrometer for Hinode - The solar optical telescope for the Hinode mission: An overview - The solar optical telescope of Solar-B (Hinode): The optical telescope assembly - Image stabilization system for Hinode (Solar-B) Solar optical telescope - Polarization calibration of the solar optical telescope onboard Hinode.